2020
DOI: 10.1371/journal.pone.0227825
|View full text |Cite
|
Sign up to set email alerts
|

Detection and density of breeding marsh birds in Iowa wetlands

Abstract: Accounting for imperfect detection is an important process when obtaining estimates of density or abundance for breeding birds, and this is particularly true when researchers are monitoring birds to assess the success of restored wetlands. Due to the dramatic decline in areal cover and habitat quality, wetland restoration in the Prairie Pothole Region (PPR) is critically important to breeding birds. The Shallow Lakes Restoration Project (SLRP), a partnership between the Iowa Department of Natural Resources and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 91 publications
(122 reference statements)
1
2
0
Order By: Relevance
“…We examined the utility of ARUs to study springtime avian habitat use within agricultural landscapes. We found that, in addition to documenting species richness of vocalizing species springtime avian communities, ARUs generated species-level detection probabilities similar to or higher than studies on breeding season occupancy of grassland birds (Sidie-Slettedahl et al 2015, West et al 2016, Rigby and Johnson 2019, Vanausdall and Dinsmore 2020, though we conducted more surveys. Several focal migratory species showed significant trends in springtime habitat associations.…”
Section: Discussionsupporting
confidence: 60%
“…We examined the utility of ARUs to study springtime avian habitat use within agricultural landscapes. We found that, in addition to documenting species richness of vocalizing species springtime avian communities, ARUs generated species-level detection probabilities similar to or higher than studies on breeding season occupancy of grassland birds (Sidie-Slettedahl et al 2015, West et al 2016, Rigby and Johnson 2019, Vanausdall and Dinsmore 2020, though we conducted more surveys. Several focal migratory species showed significant trends in springtime habitat associations.…”
Section: Discussionsupporting
confidence: 60%
“…Regarding the detectability of the species, our results provide relevant information for the development of monitoring programs suitable for the species, since considering the factors that influence the probability of detection can improve the precision of the estimates (Vanausdall & Dinsmore 2020). Furthermore, this is the first study that has examined the importance of considering factors that may influence the probability of detection when estimating the density or abundance of South American swans.…”
Section: Discussionmentioning
confidence: 86%
“…Assuming a detection probability of only 50%, a realistic situation for such large and often vegetated wetlands (Einoder et al . 2018, Vanausdall & Dinsmore 2020), the three most important sites (Tokar game reserve as well as Er Roseires and Khashm El Girba reservoir dams) would then qualify as sites of international importance according to Ramsar criteria 5 (Ramsar Secretariat 2014). They would thus represent a higher priority target in the national IWC programme.…”
Section: Discussionmentioning
confidence: 99%